2020
DOI: 10.1155/2020/9592124
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Prenatal Care and Associated Factors among Pregnant Women at Public Health Facilities of Wogera District, Northwest Ethiopia

Abstract: Background. Prenatal care refers to services a pregnant woman receives during pregnancy to ensure a healthy outcome for herself and her newborn. However, only limited studies have so far been done to assess the quality of prenatal care in the study area. Thus, this study is aimed at assessing the quality of prenatal care and associated factors at public health facilities in Wogera district, northwest Ethiopia. Methods. An institution-based cross-sectional study was conducted in Wogera district from March to Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
29
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 17 publications
11
29
1
8
Order By: Relevance
“…On the other hand, a study conducted by Sharma et al (2017) to determine the Inequities in the quality of antenatal and delivery care in Kenya, found that the quality structure was low. Also, Egyptian study conducted by Ismail and Essa (2017) and a recent study conducted by Kassaw et al (2020) found that the quality structure of ANC was poor.…”
mentioning
confidence: 96%
“…On the other hand, a study conducted by Sharma et al (2017) to determine the Inequities in the quality of antenatal and delivery care in Kenya, found that the quality structure was low. Also, Egyptian study conducted by Ismail and Essa (2017) and a recent study conducted by Kassaw et al (2020) found that the quality structure of ANC was poor.…”
mentioning
confidence: 96%
“…Não foi usada a variável "mora com parceiro" no modelo da regressão logística múltipla, pois ela apresenta categoria com valores abaixo de -Pi et al, 2016;Kassaw, Debie, Geberu, 2020;Koroma et al, 2017;Kyei et al, 2012;Tsunechiro et al, 2018).…”
Section: Reprodutivaunclassified
“…Possivelmente, essas diferenças sejam resultantes da variedade de critérios de avaliação, da organização do sistema de saúde, bem como dos contextos sociodemográficos e econômicos de cada país ou região, que podem determinar a oferta e acesso aos serviços de saúde de qualidade. No caso dos países africanos, constituem critérios de avaliação da qualidade do pré-natal, em geral, a IG do início do pré-natal (entre 12 a 16 semanas), a realização de quatro ou mais consultas, exames de HIV, sífilis, hemograma, tipagem sanguínea, glicemia, exame de urina, tratamento preventivo da malária, oferta do sulfato ferroso, administração da vacina antitetânica, peso da mulher, medição da altura uterina, auscultação do batimento fetal, informações de estrutura física e disponibilidade de material (Afulani et al, 2019;Fagbamigbe;Idemudia, 2015;Kassaw, Debie, Geberu, 2020;Koroma et al, 2017;Kyei et al, 2012) -Pi et al, 2016;Zanconato et al, 2006).…”
Section: Reprodutivaunclassified
See 2 more Smart Citations